Mitochondrial DAMPs as a critical driver in the development of acute graft versus host disease and emerging mitochondria targeted therapeutic strategies - Raguraman, Vasantharaja; Prabhu, Yogamaya Divakar; Velmurugan, Gopal Viswanathan; Hildebrandt, Gerhard C.; Palaniyandi, Senthilnathan (Frontiers in Immunology, 2026)
Mitochondrial fusion and fission regulate mitochondrial morphology and homeostasis, both of which are essential for maintaining cellular health. Free mitochondria and mitochondrial-containing extracellular vesicles have emerged as key mediators of pathological processes. Conditioning regimens for allogeneic hematopoietic cell transplantation (HCT) damage and lead to impaired mitochondrial function, including biogenesis and respiration, as well as elevated reactive oxygen species (ROS), which contribute to the development of inflammatory conditions as well as activation of antigen presenting cells, the latter being key players in acute graft versus host pathophysiology (GVHD). This leads to increased T-cell activation and proliferation, which increases alloreactivity and drives GVHD. Dysregulated mitochondrial dynamics lead to the release of mitochondrial DNA and formylated peptides, which act as Damage-Associated Molecular Patterns (DAMPs) and trigger cellular homeostatic imbalances, ultimately leading to more inflammation. The understanding that mitochondrial dysfunction contributes to GVHD offers novel therapeutic strategies, including blocking DAMP signaling and modulating immune cell metabolism to restore mitochondrial health. This review aims to understand mitochondrial homeostasis in both recipient and donor cells. This is crucial for understanding GVHD pathophysiology and developing mitochondria-targeted therapies or mitochondrial transfer strategies as potential therapeutic interventions for GVHD.